Transforming Tradition: From One Instructor to an Entire Department. Issue 3 (28th May 2021) - McClendon, David M.; Weller, Kirk; Trouba, Jerome; Brigance, Sandra; Dekker, Michael
Abstract : In this paper, we describe the evolution of calculus instruction at a mid-sized, career-oriented, comprehensive public university. Changes in practice, that began with a single faculty member implementing technology as a tool for student inquiry, have spread to other department faculty via support from an internal grant, workshops, and the use of shared "living" course materials rather than traditional texts. This evolution in ways of thinking led to the formation of a working group charged with the assessment of calculus instruction. By focusing its attention on an analysis of student outcomes, the working group has come up with further recommended reforms to calculus instruction, both in terms of pedagogical approaches and content coverage. These recommendations have the potential to support further cultural change in the department (including similar reform in other courses), ultimately leading to greater student success.